Factors Influencing Industrial Waste Applying Information Technology and Managing Information Systems Towards Minimizing Waste Management - Cha, Kian Teow; Ma, Junzhe; Chong, Kim Mee (INTI International University, 2024)
This study explores the surging of demand for manufactured products with the increasing of world’s population. While the manufacturing sector is essential in meeting this demand, it also faces the significant challenge of reducing the environmental impact of industrial waste. Manufacturing industrial waste primarily arises from by-products, over-extraction of natural resources, and inefficient production processes. Poor management of manufacturing processes would lead to adverse social impacts to human health, natural resources depletion, ecosystem destruction, and contribute to global warming and climate change. Additionally, improper waste disposal can result in financial losses and legal penalties for non-compliance with environmental regulations. Hence, it is imperative for the manufacturing sector to leverage emerging technologies and management strategies to mitigate these challenges. Therefore, this study used a quantitative approach to analyse primary data collected from the survey questionnaire to examine the relationship between independent and dependent variables. Combination of financial, technical, social, and governmental factors addressed in this project underscores the multifaceted approach required for effective waste management